Comprehensive Evaluation on the Yield, Quality, and Water-Nitrogen Use Efficiency of Mountain Apple Under Surge-Root Irrigation in the Loess Plateau Based on the Improved TOPSIS Method - Hao, Kun; Fei, Liangjun; Liu, Lihua; Jie, Feilong; Peng, Youliang; Liu, Xiaogang; Khan, Sher Aslam; Wang, Dong; Wang, Xiukang (Frontiers in Plant Science, 2022)
The purpose of this study was to make known the controlling effects of water and nitrogen coupling on yield, quality and water-nitrogen utilization effectiveness of mountain apple under surge-root irrigation in the Loess Plateau. In order to optimize water and nitrogen irrigation system of the superior quality and high yield, seven years was selected for the mountain apple test material. The trial was designed with four tiers of irrigation, i.e., full irrigation (FI: 85–100%θf, where θf is the field capacity), light deficit irrigation (DIL: 70–85%θf), moderate deficit irrigation (DIM: 55–70%θf) and severe deficit irrigation (DIS: 40–55%θf), and three tiers of nitrogen, i.e., high nitrogen (NH: 600 kg ha-1), middle nitrogen (NM: 400 kg ha-1) and low nitrogen (NL: 200 kg ha-1). The subjective weight attained by analytic hierarchy methods and the objective weight achieved by enhanced coefficient of variation method were examined to find the comprehensive weight based on the notion of game hypothesis. Then, the weighted TOPSIS process was utilized to comprehensively assess the yield, quality, and water-nitrogen use efficiency of apples, and a binary quadratic regression model was created between comprehensive evaluation index and water-nitrogen inputs. The results showed that the effects of irrigation and nitrogen levels on the fruit yield, irrigation water use efficiency (IWUE), total water use efficiency (TWUE), nitrogen partial factor productivity (NPFP), and quality of mountain apples were considerable (P < 0.05). The apple yield and TWUE first improved and then diminished with an escalating quantity of water-nitrogen inputs, the IWUE diminished with an boost in the irrigation quantity, the NPFP dwindled when the nitrogen amount was increased. The best water and nitrogen inputs for apple yield, quality or water-nitrogen use efficiency were dissimilar. The best comprehensive evaluation index was DILNM treatment, and the worst comprehensive evaluation index was DISNL treatment, based on TOPSIS system. The interval of irrigation and nitrogen attained from the mathematic model ranged in 95–115 mm and 470–575 kg ha-1, respectively.